The impact of urban management strategy on establishing new cities: global concepts and experiences - Abduljabar, Rania; Ibrahim , Mustafa (Al-Adab Journal, 2025)
In order to achieve the goals of urban management in establishing new urban settlements known as new cities, there are several skills that influence its goals, which are intellectual skills that enter into the formation of the comprehensive vision between planning, implementation and human skills, which require benefiting from expertise and scientific staff, in addition to technical skills that include knowing the potential of the sites available for establishing new cities and studying them comprehensively before implementation. Achieving these skills according to studied strategies and planning methodology will achieve urban management strategies at the level of technical services and providing suitable housing in addition to the economic strategy that attracts residents to new cities. These cities differ according to the nature of the site, characteristics and available capabilities, as the problem lies in choosing sites for new cities without an integrated standard planning methodology, and without a prior study of the urban structure surrounding these sites, which causes problems in the urban prosperity of these cities and their failure to perform the expected role. This research sheds light on the most prominent global experiences in the field of new cities, leading to an analysis of the most important urban management strategies that were achieved in the selected experiences.